Development of Plant-Derived Bispecific Monoclonal Antibody Targeting PD-L1 and CTLA-4 against Mouse Colorectal Cancer - Bulaon, Christine Joy I.; Khorattanakulchai, Narach; Rattanapisit, Kaewta; Sun, Hongyan; Pisuttinusart, Nuttapat; Phoolcharoen, Waranyoo (Planta Medica, 2024)
Checkpoint blockade immunotherapy has revolutionized cancer treatment, with monoclonal antibodies targeting immune checkpoints, yielding promising clinical benefits. However, with the advent of resistance to immune checkpoint inhibitor treatment in clinical trials, developing next-generation antibodies with potentially increased efficacy is critical. Here, we aimed to generate a recombinant bispecific monoclonal antibody for dual inhibition of programmed cell death protein 1/programmed cell death ligand 1 and cytotoxic T-lymphocyte-associated protein 4 axes. The plant system was used as an alternative platform for bispecific monoclonal antibody production. Dual variable domain immunoglobulin atezolizumab × 2C8 is a plant-derived bispecific monoclonal antibody that combines both programmed cell death ligand 1 and cytotoxic T-lymphocyte-associated protein 4 blockade into a single molecule. Dual variable domain immunoglobulin atezolizumab × 2C8 was transiently expressed in Nicotiana benthamiana and the expression level was determined to be the highest after 4 days of infiltration. The size and assembly of the purified bispecific monoclonal antibody were determined, and its function was investigated in vitro and in vivo. The molecular structures of plant-produced dual variable domain immunoglobulin atezolizumab × 2C8 are as expected, and it was mostly present as a monomer. The plant-produced dual variable domain immunoglobulin atezolizumab × 2C8 showed in vitro binding to programmed cell death ligand 1 and cytotoxic T-lymphocyte-associated protein 4 proteins. The antitumor activity of plant-produced bispecific monoclonal antibody was tested in vivo by treating humanized Balb/c mice bearing a CT26 colorectal tumor. Plant-produced dual variable domain immunoglobulin atezolizumab × 2C8 significantly inhibited tumor growth by reducing tumor volume and weight. Body weight changes indicated that the plant-produced bispecific monoclonal antibody was safe and tolerable. Overall, this proof of concept study demonstrated the viability of plants to produce functional plant-based bispecific immunotherapy.
Keywords: Nicotiana benthamiana; Solanaceae; DVD-AT2C; bispecific antibody; checkpoint blockade; immunotherapy